Sugammadex-Associated Hypotension, Bradycardia, Asystole, and Death. (10th June 2020) - Mirza, Kazim; Landoski, Kathryn; Thakar, Dilip; Heir-Singh, Jagtar; Jackson, Timothy; Kassab, Cynthia
Abstract : On December 16, 2015, the Food and Drug Administration (FDA) in the United States approved sugammadex (Bridion, Merck and Co), a modified gamma-cyclodextrin, to be used as a reversal agent. It is a first and unique selective nondepolarizing steroidal muscle relaxant (NDSMR) binding agent with a great affinity for rocuronium and vecuronium. However, there have been several recently published case reports of bradycardia and asystole immediately after sugammadex administration for the reversal. This report presents a case of sugammadex administration followed by rapidly progressing bradycardia leading to asystole and subsequent death. The family has provided the written consent to share this case report.